1994
DOI: 10.1051/mmm:0199400504-6037300
|View full text |Cite
|
Sign up to set email alerts
|

SEM, ToF-SIMS and LFM morphological study of an heterogeneous polymeric surface

Abstract: The surface morphology of films prepared with 20% of PP and 80% of PET has been studied by means of various methods: scanning electron microscopy (SEM), time of flight secondary ion mass spectrometry (ToF-SIMS) and lateral force microscopy (LFM). The three methods revealed an heterogeneous surface with a continuous phase including nodules whose size ranges from approximately 1 03BCm to more than 100 03BCm. ToF-SIMS analyses identified the chemical nature of this heterogeneity: the continuous phase is PET and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the ®eld of polymers, distinct phases may be useful to study blends or mixtures. Nysten et al (1994) have used scanning electron microscopy (SEM), TOF S-SIMS and lateral force microscopy to study a heterogeneous polymeric surface, obtained by compression molding of two incompatible polymers PP (20%) and PET. The surface contained nodular inclusions of about 1± 100 mm.…”
Section: Cnmentioning
confidence: 99%
“…In the ®eld of polymers, distinct phases may be useful to study blends or mixtures. Nysten et al (1994) have used scanning electron microscopy (SEM), TOF S-SIMS and lateral force microscopy to study a heterogeneous polymeric surface, obtained by compression molding of two incompatible polymers PP (20%) and PET. The surface contained nodular inclusions of about 1± 100 mm.…”
Section: Cnmentioning
confidence: 99%
“…It has been shown that quantitative analyses can be performed with static SIMS on certain polymer blends, such as polystyrene/poly(vinyl ethyl ether), , polycarbonate/polystyrene, polycarbonate/poly(methyl methacrylate), polypropylene/poly(ethylene terephthalate), polystyrene/poly(2,6-dimethyl-1,4-phenylene oxide), poly(vinyl chloride)/poly(methyl methacrylate), and poly(sebacic anhydride)/poly( dl -lactide acid). , In the above systems, the intensities of some SIMS characteristic peaks unique to each component can be related to the bulk composition or the surface composition determined by XPS. The strong relationship between SIMS peak intensities and the copolymer or polymer blend composition showed that SIMS can be used as a quantitative technique.…”
mentioning
confidence: 99%
“…In UCLouvain, all these new exciting tools for nanosciences arrived in the nineties. The first AFM and STM were acquired in 1994 [13,14]. The first DFT and TB simulators were developed and used in the early nineties [15][16][17][18] and the ABINIT project was launched officially in 1997 [19].…”
Section: Introductionmentioning
confidence: 99%